ANALISIS PERBANDINGAN KUAT TEKAN BETON MENGGUNAKAN AGREGAT HALUS CIKALONG DENGAN AGREGAT HALUS GALUNGGUNG - Nurman Sidik, Nurman Sidik; Asniar, Novi; Nurdianto, Risnandar (JITSi : Jurnal Ilmiah Teknik Sipil, 2022)
Abstract— The city of Tasikmalaya is a sand-producing area with a source from Mount Galunggung. The sand has a good quality that meets the standards. Therefore, it is not uncommon for residents from outside the region to also flock to use this sand, but the availability of Galunggung sand is decreasing over time. To minimize the use of sand from Mount Galunggung, another alternative source of sand is used, namely the Ciwulan River in Cikalong District. There is a need for testing to determine the value of water content, specific gravity and water absorption in the aggregate material, and the value of the compressive strength of concrete at the age of 3, 7, and 28 days from two different types of fine aggregate material and which fine aggregate has the value of the compressive strength of concrete. the highest. The results of testing the value of the water content of the Cikalong fine aggregate is 1.24% and for the Galunggung fine aggregate, it is 2.46%. The results of testing the specific gravity of fine aggregate for Cikalong are 1.90 and for Galunggung fine aggregate it is 2.54. The results of the water absorption test for Cikalong fine aggregate are 2.24% and for Galunggung fine aggregate it is 1.91%. Based on these data, the greatest compressive strength of concrete at the age of 28 days is a mixture of fine aggregate Cikalong of 22.98 MPa. Keywords — Cikalong fine aggregate, Galunggung fine aggregate, moisture content, specific gravity and water absorption, concrete compressive strength. Abstrak—Kota Tasikmalaya merupakan wilayah penghasil pasir dengan sumber dari Gunung Galunggung. Pasir tersebut memiliki kualitas yang baik yang memenuhi standar. Oleh karena itu tak jarang para penduduk luar wilayah juga berbondong-bondong untuk menggunakan pasir ini, namun ketersediaan pasir Galunggung semakin berkurang seiring berjalannya waktu. Untuk meminimalkan penggunaan pasir dari Gunung Galunggung, maka digunakan alternatif lain sumber penghasil pasir yaitu Sungai Ciwulan di Kecamatan Cikalong. Untuk perlu adanya pengujian untuk mengetahui nilai dari kadar air, berat jenis dan penyerapan air pada material agregat, nilai kuat tekan beton pada umur 3, 7 dan 28 hari dari dua jenis bahan agregat halus yang berbeda dan agregat halus manakah yang memiliki nilai kuat tekan beton yang paling tinggi. Hasil pengujian nilai kadar air agregat halus cikalong sebesar 1,24% dan untuk agregat halus galunggung sebesar 2,46%. Hasil pengujian berat jenis agregat halus cikalong sebesar 1,90 dan untuk agregat halus galunggung sebesar 2,54. Hasil pengujian penyerapan air agregat halus cikalong sebesar 2,24% dan untuk agregat halus galunggung sebesar 1,91%. Berdasarkan data tersebut dihasilkan nilai kuat tekan beton terbesar pada umur 28 hari yaitu campuran agregat halus cikalong sebesar 22,98 MPa. Kata kunci — Agregat halus Cikalong, agregat halus Galunggung, kadar air, berat jenis dan penyerapan air, kuat tekan beton.